2007
DOI: 10.2139/ssrn.1015507
|View full text |Cite
|
Sign up to set email alerts
|

Generosity and Philanthropy: A Literature Review

Abstract: We present an overview of the academic literature on philanthropy, divided in two parts. In part one, we discuss the question of who gives how much; in part two, we discuss the question of why people give. In part one, we survey the literature on characteristics of individuals and households that are related to giving. In part two, we identify eight mechanisms as the most important forces that drive giving: (1) awareness of need; (2) solicitation; (3) costs and benefits; (4) altruism; (5) reputation; (6) psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
168
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(175 citation statements)
references
References 454 publications
(777 reference statements)
4
168
1
2
Order By: Relevance
“…In the literature many motives for donating to charity are mentioned, see Bendapudi, Singh and Bendapudi (1996), Sargeant (1999) and Bekkers and Wiepking (2007) for reviews. The most studied motives that have relevance across multiple charities are 1) altruism 2) a feeling of joy of giving or 'warm glow' 3) feelings of guilt and 4) prestige.…”
Section: Theoretical Background and Predictions For Competitive Effectsmentioning
confidence: 99%
“…In the literature many motives for donating to charity are mentioned, see Bendapudi, Singh and Bendapudi (1996), Sargeant (1999) and Bekkers and Wiepking (2007) for reviews. The most studied motives that have relevance across multiple charities are 1) altruism 2) a feeling of joy of giving or 'warm glow' 3) feelings of guilt and 4) prestige.…”
Section: Theoretical Background and Predictions For Competitive Effectsmentioning
confidence: 99%
“…We include controls for several types of resources that are correlated with secular and religious philanthropic behaviour (see for example Musick & Wilson 2008;Bekkers & Wiepking 2007;Smith et al 2008, Finke et al 2006, Iannaccone 1997, and Hoge 1994.…”
Section: Analytical Strategymentioning
confidence: 99%
“…On the basis of an extensive review, Bekkers and Weipking 24 concluded that there is a need to do additional research to understand crossnational differences in philanthropy. In addition to understanding the relationship of religiosity with charitable giving, it is important to understand underlying motivations for charitable giving.…”
Section: Covariates Of Religiositymentioning
confidence: 99%